2021
DOI: 10.1039/d1ra03390e
|View full text |Cite|
|
Sign up to set email alerts
|

Binding modes of methyl α-d-glucopyranoside to an artificial receptor in crystalline complexes

Abstract: Complexes formed between methyl α-d-glucopyranoside and an artificial receptor represent a valuable source of information about the basic molecular features of carbohydrate recognition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

7
2

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 59 publications
2
5
0
Order By: Relevance
“…In addition to the crystalline complex shown in Figure 5 a, crystal structures of other 2:1 receptor-sugar complexes were obtained ( Figure 5 c), [ 18 , 19 ] confirming the binding motif observed in the first crystal structure. The carbohydrate is embedded between two benzene rings, thus forming CH∙∙∙π interactions with these central aromatic moieties of the two receptor molecules (for examples of other macrocyclic carbohydrate receptors, see refs.…”
Section: Resultssupporting
confidence: 69%
See 1 more Smart Citation
“…In addition to the crystalline complex shown in Figure 5 a, crystal structures of other 2:1 receptor-sugar complexes were obtained ( Figure 5 c), [ 18 , 19 ] confirming the binding motif observed in the first crystal structure. The carbohydrate is embedded between two benzene rings, thus forming CH∙∙∙π interactions with these central aromatic moieties of the two receptor molecules (for examples of other macrocyclic carbohydrate receptors, see refs.…”
Section: Resultssupporting
confidence: 69%
“…[ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 ]; for recent reports on binding studies, see refs. [ 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ]). On the one hand, such model systems help to better understand the phenomena of biological carbohydrate-mediated processes, and on the other hand, X-ray structural analyses of the protein-carbohydrate complexes [ 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 ] serve as a source of ideas for the design of the biomimetic systems.…”
Section: Introductionmentioning
confidence: 99%
“…The 1,3,5-trisubstituted 2,4,6-trialkylbenzene scaffold has shown to be valuable for the construction of various artificial receptors (Hennrich & Anslyn, 2002). In the course of our research work, we have successfully used this molecular scaffold in the design of acyclic and macrocyclic receptors for neutral (Mazik, 2009(Mazik, , 2012Amrhein et al, 2016;Koch et al, 2016;Amrhein & Mazik, 2021;Ko ¨hler et al, 2020Ko ¨hler et al, , 2021 and ionic substrates (Geffert et al, 2013;Stapf et al, 2015;Schulze et al, 2018). Our studies on the molecular recognition of carbohydrates have shown that the participation of different types of recognition groups in the complexation of the substrate favourably influences the binding process (Stapf et al, 2020a,b;Kaiser et al, 2019).…”
Section: Chemical Contextmentioning
confidence: 99%
“…The binding properties of these compounds depend on the nature of their building blocks, among others, the type of bridging units that connect two aromatic platforms (Lippe & Mazik, 2013, 2015Amrhein et al, 2016. The design of such receptor architectures was inspired by the results of our crystallographic studies on receptor-carbohydrate complexes (Mazik et al, 2005; for recent examples, see Ko ¨hler et al, 2020Ko ¨hler et al, , 2021. For the syntheses of macrocycles consisting of benzenebased bridges, various 2-or 5-substituted benzene-1,3-dicarbaldehydes have proven to be useful starting materials.…”
Section: Chemical Contextmentioning
confidence: 99%